Spiritual Development in 10 Minutes 38 Seconds in This Strange World by Elif Shafak - Khadija; Dr. Muhammad Akbar Khan; Zainab Akram (University of Chitral Journal of Linguistics and Literature, 2024)
The spiritual development in this study relates to the real purpose of life, which exerts influence on every person’s activity. It is not about religious affiliation or becoming more spiritual.it is the innate realization and connection of oneself with the divine. This study delves into the canon of spirituality, William C. Chittick, by contextualizing the quest for meaning, identity, and transcendence with explicit reference to Elif Shafak’s novel Ten Minutes 38 Seconds in this Strange World. By scrutinizing the selected novel through the lens of Chittick’s spiritual underpinnings, this paper unmasks how a spiritual journey seeks nothing in the sense of achieving worldly gains. By doing so, this study investigates the elements of spiritual development in ordinary life with the quest for truth and meaning. It also indicates that without being prejudiced, a person examines and transforms himself. The spiritual path in Chittick and Shafak’s novel portrays the situation clearly. It gives the essence of spiritual development without being confined to typical religious norms, which makes this study a significant aspect of inner change.